PERANCANGAN FASILITAS WISATA BERBASIS PARTISIPASI MASYARAKAT DI KAMPUNG WISATA TEMATIK PANUNGGANGAN UTARA TANGERANG - Imaniar Sofia Asharhani; Alfonsus Grandy Wiranata; Lidwina Pia Pratama Dewi; Eiffel Eiffel; Sallie Sallie (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2022)
The Covid-19 provides a cautionary about the importance of resilient communities. The active role of the community in environmental development is very important to develop sustainable village. In line with the Thematic Tourism Village Program by the Tangerang City government, residents of North Panunggangan Village are in the process of developing one of their tourist destinations, namely the Peng'Angguran House. The participation of community is currently at the stage of consultation, discussion and initial design. Furthermore, aspirations for proposed building functions by the community, data collection of types of community activities, selection of appropriate locations, and prediction of construction cost budgets are needed in these stages. The design process is user centered, hence community is not just recipient of governmental policies. The implementation method begins with the preparatory stage, that is mapping the potential for area development in the form of group consultations with community. The next stage is a group discussion with to design tourism areas and buildings that function to accommodate tourism in the community. Hopefully proposed building will be sustainable in accordance with the needs of its users. The final stage is an alternative initials to the design of the cafe and the design of the open area, based on the proposed function of the space program agreed upon by the community. Design implementation is hoped that the people will be able to use these facilities optimally. Especially people who live near the location of the Peng'Angguran House, Kebon Nanas, North Panunggangan Village, Pinang District, Tangerang City.